Center-Pivot-Irrigated Sunflowers Cost-Return Budget in Western Kansas - Ibendahl, Gregg; O'Brien, Daniel M.; Haag, Lucas; Falk Jones, Jeanne; Holman, John (My University, 2015)
The cost-return projection estimates the cost of producing center-pivot-irrigated sunflowers in western Kansas.
MF800_2015_04
Keywords: MF800; Economics; Crops; MF